Inclusion strategies that work! research-based methods for the classroom - Karten, Toby J.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2010)
Are you ready to make inclusion work in your classroom? Now in its second edition, this best-selling guide shows how teachers can help students of all abilities learn, collaborate, and achieve. With an interactive, teacher-friendly approach, this comprehensive handbook includes new information on national mandates affecting special education and a wealth of teaching strategies supported by the latest research. It has been developed for K-12 general education and special education teachers.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Children with disabilities -- Education -- United States; Teenagers with disabilities -- Education -- United States; Inclusive education -- United States; Electronic books